2005
DOI: 10.1074/jbc.m500728200
|View full text |Cite
|
Sign up to set email alerts
|

Zhangfei Is a Potent and Specific Inhibitor of the Host Cell Factor-binding Transcription Factor Luman

Abstract: Host cell factor (HCF) was initially discovered as a cellular co-factor required for the activation of herpes simplex virus immediate early gene expression by the virion associated transactivator VP16. HCF also participates in a variety of cellular processes, although the mechanism of its action is not known. VP16 binds to HCF through a 4-amino acid motif (EHAY), which closely resembles the HCF binding domain of two cellular basic leucine-zipper proteins, Luman and Zhangfei. Luman is a powerful transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 49 publications
1
57
0
1
Order By: Relevance
“…In contrast, Zhangfei does not bind any of the known cognate sequences for b-zip proteins, nor does it activate promoters containing these sequences (23). However, Zhangfei has a profoundly repressive effect upon HCF-dependent transcription activation by Luman (30). HCF binding by both Zhangfei and Luman is required for efficient suppression by Zhangfei.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast, Zhangfei does not bind any of the known cognate sequences for b-zip proteins, nor does it activate promoters containing these sequences (23). However, Zhangfei has a profoundly repressive effect upon HCF-dependent transcription activation by Luman (30). HCF binding by both Zhangfei and Luman is required for efficient suppression by Zhangfei.…”
mentioning
confidence: 86%
“…The plasmids encoding Zhangfei (pcZF); mutant Zhangfei which is unable to bind HCF (pcZF Y224A); LuS221Op, the truncated form of full-length Luman (pcLuS221Op); LuS221Op (N160G) with a mutation in the DNA binding domain (pcLuS221Op N160G); and HCF (pSL7) have been previously described (19,23,30). The plasmid G5EC, a chloramphenicol acetyltransferase (CAT) reporter which contains five copies of the Saccharomyces cerevisiae Gal4 upstream activation signal (UAS), as well as the pM series of plasmids for constructing Gal4 fusion proteins was a gift from Ivan Sadowski.…”
Section: Cells and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, SMILE cannot bind to DNA as a homodimer (10)(11)(12). SMILE has also been reported to function as a coactivator of activating transcription factor 4 or as a corepressor of host cell factor-binding transcription factor (13,14). Previously, we have reported that SMILE is a corepressor of the estrogen receptor-related receptor g, glucocorticoid receptor (GR), constitutive androstane receptor, hepatocyte nuclear factor 4a (HNF4a), and CREBH (15)(16)(17).…”
mentioning
confidence: 99%